Research unlatched in Norway: What influences the use of Open Access and how to boost it? - Moksness, Lars (Septentrio Conference Series, 2014)
Open Access (OA) is a democratic way of publishing research and making data freely available for everyone to use. Studies have shown that OA articles enjoyed higher citation rates, and were downloaded and read more frequently than non-OA published articles. OA publications have the potential to reach a wider audience and benefit specialists and laypeople in a variety of professions, such as the law, health and industry sector. Still, the amount of research made available in OA could be a lot better. Additionally, some disciplines use OA more than others. According to a status report from UiT The Arctic University of Norway (UiT) in 2011, it is not the availability of OA archives that is lacking. Rather, the challenge lies with the amount of research made accessible in these archives. Several factors might influence the decision to make research available in OA, and the proposed study aims, ultimately, to uncover which these may be among Norwegian researchers. Subsequently, interventions will be developed and implemented to boost the use of OA in Norway. Interdisciplinary and discipline specific focus group interviews will provide the material to develop a questionnaire for the pilot study. The main study should ideally collect data nationwide, in as many universities, colleges and research institutes as possible. However, due to the scope of such a study, a preliminary study with interventions could initially be conducted at UiT. The data collected will subsequently be used for the development of interventions designed to boost OA use. One such intervention could be a marketing campaign geared towards increasing awareness of OA, possibly with some incentives to researchers for making research openly and freely available. Interventions will initially be implemented locally (UiT), but if successful on a national scale. Success could be measured by an increase in publications in OA journals and data repositories. Furthermore, a follow-up study could be conducted to ascertain the impact of the implemented interventions.